Actual Issues of the Development of Private law in the Republic of Armenia - Avetisyan, V. (Bulletin of Yerevan University C: Jurisprudence, 2019)
The report substantiates the opinion that the development of private law in the legal system of the Republic of Armenia was carried out spontaneously, by situational decisions, without a developed concept, without taking into account scientific justifications and objective problems that arise in practice.Particular attention is paid to the rethinking of private law relations in the field of public relations and the clarification of balanced relations with public law regulation. It is noted that in the future, in order to most effectively solve these problems in the Republic of Armenia, the development of private law should be based on a conceptual and knowledge-based legal policy, as a result, public and private interests will be effectively balanced, thereby contributing to the development of the private sector, the creation of social market economy based on the right of ownership, freedom of economic activity and economic competition.
Keywords: private law, public law, development of private law, development of a policy for the development of law based on scientific knowledge